To play the king [videorecording (DVD)] - Richardson, Ian, 1934-2007; Kitchen, Michael, 1948-; Davies, Andrew, 1936-; Seed, Paul; Dobbs, Michael, 1948- (House of cards., 2003)
Manipulative and corrupted English prime minister, Urquhart, has reached the pinnacle of power as the leader of his party, but the succession of a king opposed to his policies challenges Urquhart's authority.